Genomic data from Fairy penguin ( Eudyptula novaehollandiae ). ... - Pan, Hailin; Cole, Theresa; Couto, Alvarina; Bi, Xupeng; Machado, André, M.; Brejova, Brona; Fang, Miaoquan; Albertin, Caroline, B.; Zhou, Chengran; Silva, Filipe; Yang, Zhengtao; Gardner, Paul; et al. (GigaScience Database, 2019)
The Australian fairy penguin (also known as little blue penguin, blue penguin and little penguin) is one of the smallest penguins. It is found widely along the southern coastlines of Australia and the Otago coast of New Zealand. They have a slate-blue plumage. Recent genetic, morphological and behavioral research has demonstrated that the Australian fairy penguin is a separate species to the New Zealand little blue penguin, however this still remains controversial. Populations have recently declined, and they are considered as Least Concern by the International Union for Conservation of Nature (IUCN), however this assessment still classifies the Australian and New Zealand species as conspecific. We sequenced the genome of an adult Fairy penguin from Phillip Island, Victoria, Australia (provided by Peter Dann) to a depth of approximately 137x with short reads from a series of libraries with various insert sizes (250bp-20Kb). The assembled scaffolds of high quality sequences total 1.28Gb, with the contig and ...